Transformasi Biplot Simetri Pada Pemetaan Karakteristik Kemiskinan - Desy Komalasari; Mustika Hadijati; Marwan . (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2013)
The purpose of this research is to provide the new innovations on mapping of poverty characteristics in West Nusa Tenggara Province using Biplot analysis. The analysis based on matrix transformation, singular value decomposition, and matrix factorization. In this research we construct two kind of matrix transformation, that are average transformation and standarization transformation. The result of this research is symmetry Biplot, which maps the regency and poverty characteristics simultaneously. The result of Biplot mapping with average transformation obtained the value of (79.12%), while standarization transformation obtained the value of (63.11%). It can be concluded that Biplot mapping with averaging transformation is better than standarization transformation.